The Impact of International Media on the Cultural Identity of the Palestinian Society - Batat, Walaa Dawoud; Elsayed, Eman Ibrahim (Journal of Posthumanism, 2025)
This study aims to monitor and analyze the media elites' attitudes towards the impact of international media on the image of the cultural identity of the Palestinian community abroad. It seeks to identify the extent of exposure of media and cultural elites to international media, as well as to examine the role of international media in promoting Palestinian cultural authenticity from the perspective of intellectuals and media professionals. Furthermore, the study investigates the role of the Palestinian community in preserving its cultural identity in the face of international media influences and highlights the main challenges Palestinian media faces in maintaining the authenticity of its cultural identity.The study was conducted using a purposive sample consisting of 20 academics, media professionals, and intellectuals. Through in-depth interviews, the main findings indicate that there is a variation in the patterns of exposure to international media among the media elites and intellectuals. This reflects an advanced professional awareness of the media's role and the necessity of following international media coverage, particularly regarding the Palestinian issue. There is a preference for selective exposure linked to major events. The results also show that media elites and cultural figures rely on international media as analytical sources, with varying degrees of dependence based on the nature of the media outlet. Some exhibit critical awareness, prompting them to verify the credibility of information from multiple sources. International media outlets demonstrate clear differences in how they address Palestinian culture. Some media outlets that align with the Israeli narrative use culture as a tool to marginalize Palestinian identity and distort its heritage, while media outlets supporting the Palestinian cause fail to separate cultural from political narratives, which limits the recognition of culture as an independent value.